Antioxidant Activity Assay of Methanol Extract Fractions From Red Lemongrass (Cymbopogon nardus L.) Stems Using the Dpph Method (International Forum of Researchers and Lecturers, 2025)
Background: For generations, herbal plants have played a vital role in traditional medicine in Indonesia. One such plant is red lemongrass (Cymbopogon nardus L.), which has shown promise as a source of natural bioactive compounds. This plant contains a variety of phytochemicals, including flavonoids, polyphenols, alkaloids, and essential oils. Flavonoid compounds such as flavones, flavanones, isoflavones, anthocyanins, and leucoanthocyanidins are particularly noted for their antioxidant functions. Objective: The primary aim of this research was to evaluate the antioxidant activity and determine the IC₅₀ values of the n-hexane and n-butanol fractions derived from the stem extract of red lemongrass collected in Wakatobi Regency. Methods: The extraction process began with maceration using methanol as the initial solvent, followed by a liquid-liquid extraction utilizing n-hexane and n-butanol to separate fractions. Antioxidant activity was assessed through the DPPH radical scavenging method at three concentrations: 50, 100, and 150 ppm. Results: The antioxidant assay revealed that the IC₅₀ value of the n-hexane fraction was 3.458 ppm, while the n-butanol fraction showed a significantly stronger activity with an IC₅₀ of 0.658 ppm. For comparison, vitamin C—used as a positive control—had an IC₅₀ value of 0.585 ppm. Both fractions fell within the “very strong antioxidant” category (IC₅₀ < 10 ppm). Conclusion: The n-butanol fraction demonstrated the highest antioxidant activity, closely approaching the efficacy of vitamin C. These results underline the therapeutic potential of red lemongrass and provide a scientific foundation for its further exploration in pharmaceutical and nutraceutical product development.